PELAKASANAAN PASAL 7 AYAT (2) HURUF b UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 34 TAHUN 2004 TENTANG TNI DALAM SISTEM KETATANEGARAAN INDONESIA (Studi Terhadap Penanggulangan Bencana Daerah Oleh Kodam XII/Tpr di Provinsi Kalimantan Barat) - MUHAMMAD WIRYAWAN RADIYANTO, SH A.2021141059, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2016)
ABSTRACTThis thesis discusses exercising Article 7 Paragraph (2) Letter B Law of the Republic of Indonesia Number 34 Year 2004 on TNI In Indonesia Administration System (Study Against Regional Disaster By KODAM XII / TPR in West Kalimantan Province). The method used in this research is normative-sociological approach. From the results of this thesis can be concluded that the implementation of Article 7 Paragraph (2) Letter b Law Act No. 34 of 2004 About TNI in the system of state administration of the Republic of Indonesia, the TNI Indonesia as the main component, whereas in the face of non-military threats put organizations government outside the defense sector as the main element. In the deployment and use of military force, TNI under the President. But specifically in terms of the deployment of Indonesian National Armed Forces to confront armed threats, the President must be approved by the House of Representatives, except in emergencies. But the deployment of military force in non-war military operations, authority and responsibility for the deployment of military force currently on the President without the approval of the House of Representatives, but as elected representatives of the Board of Representatives must also approve the deployment of military force in non-war military operations. That the implementation of Military Operations Other Than War by TNI regional military command XII / TPR In West Kalimantan in relation to the role and tasks of military command in disaster management is expected to create a military front to the